Optimasi Penjadwalan Pengangkutan Sampah Secara Adaftif Menggunakan Algoritma Tabu Search - Ahmad, Suprian; Ikhsan, Muhammad (Journal of Computer System and Informatics (JoSYC), 2025)
This research aims to optimize waste transportation scheduling adaptively using the Tabu Search algorithm. Inefficient waste management can lead to increased operational costs and accumulation of waste, so an adaptive optimization approach is needed. Data collection techniques in this research include direct observation, interviews with related parties, and literature study to obtain relevant data. The data collected includes the initial schedule for transporting waste, a list of villages in the three sub-districts, and the distance traveled by the waste transport fleet. The implementation of the Tabu Search algorithm was carried out with the parameters tabu_tenure = 5 and max_iterations = 100. The research results showed that this algorithm was successful in optimizing the waste transportation route, with a total optimal cost of 35.1 in Natal District, 17.5 in Panyabungan Kota District, and 11.5 in Kotanopan District. This optimization process increases the operational efficiency of waste transportation by reducing costs and travel time. In addition, the Tabu Search algorithm is able to overcome complex route problems by finding better solutions than conventional methods. Thus, this research proves that the Tabu Search algorithm can be an adaptive solution for more effective and efficient waste management in Mandailing Natal, and has the potential to be applied in other areas with similar conditions.